Managing Land Borders and Smuggling of Food Commodities in Saki South-Western Nigeria: Socio-Economic Implications (Journal of Management and Social Sciences, 2018)
Border is one of the most visible signs of the sovereignty of a state on its territory. Inspite of the resilient efforts of Nigeria’s border security agencies to ensure thesafeguarding of Nigeria's territorial sovereignty, smuggling remains unabated and itsdynamics is characterised with strong link between the smugglers and itineraries. Themain objective of this paper is to examine the socio-economic effects of smuggling offood commodities from Republic of Benin to Nigeria through Okerete borderlandroute, Saki. The methodology used for the paper involves descriptive survey designwhile interviews were conducted among the patrol teams of custom officers in Saki,and secondary sources such as journal article, internet materials and current situation inthe country serves as sources of data collections. The paper concluded that the spate ofsmuggling of foods commodities mostly rice and frozen foods across Saki borderlandshas undermined income generation, rule of law, social vices in the communities,uncontrolled market economy and price fluctuation of commodity like rice andvegetable oil, health deterioration from these substances, and encourage drop-out (childabuse) in these communities.KeywordsBorder, smuggling, food commodity, border management